2020
DOI: 10.1021/acs.jpcc.0c07144
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Syngas Combustion on a Defective NiO Surface for Chemical Looping Combustion: Oxygen Migration and Vacancy Effects

Abstract: A thorough theoretical analysis of vacancy effects on syngas combustion was conducted for the chemical looping combustion (CLC) process using NiO as an oxygen carrier (OC). A density functional theory (DFT) analysis was conducted to provide new insights into the effects of surface vacancies on OC behavior such as O migration, syngas adsorption, and syngas oxidation. The results showed that the vacancies are expected to promote the subsequent oxidation reactions, which might come from the lower state energies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 59 publications
2
13
0
Order By: Relevance
“…It was reported that defects (e.g., oxygen vacancies) on the surface of oxygen carriers exhibited a significant influence on the reactivity . The existence of surface oxygen vacancies could effectively activate the C–H bonds. , Compared to the perfect surface, the energy barrier of CH 4 dissociation on the O-defective surface is clearly reduced.…”
Section: Reactivity and Reaction Mechanism Of Single Oxygen Carriersmentioning
confidence: 99%
“…It was reported that defects (e.g., oxygen vacancies) on the surface of oxygen carriers exhibited a significant influence on the reactivity . The existence of surface oxygen vacancies could effectively activate the C–H bonds. , Compared to the perfect surface, the energy barrier of CH 4 dissociation on the O-defective surface is clearly reduced.…”
Section: Reactivity and Reaction Mechanism Of Single Oxygen Carriersmentioning
confidence: 99%
“…Yuan et al clarified the reaction mechanism of syngas combustion by NiO . Yuan et al also used DFT to analyze the adsorption principle of syngas and lattice oxygen transfer mechanism on the surface of pure NiO (100) behavior. , …”
Section: Introductionmentioning
confidence: 99%
“…The rational design and selection of suitable oxygen carriers with both high reactivity and durability are crucial for chemical looping processes. 15 Metal oxides, such as Fe 2 O 3 , 16 NiO, 17 and CuO, 18 have drawn special focus and been investigated as oxygen carrier materials for chemical looping applications. Among all the candidates, Fe 2 O 3 is the most widely studied and employed oxygen carrier in that it possesses high oxygen capacity, low cost and high abundance.…”
Section: Introductionmentioning
confidence: 99%